Evaluation of (111)In-Labeled Cyclic RGD Peptides: Tetrameric Not Tetravalent - Chakraborty, Sudipta (2010)
This report presents the synthesis and evaluation of (111)In(DOTA-6G-RGD(4)) (DOTA = 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetracetic acid; 6G-RGD(4) = E{G(3)-E[G(3)-c(RGDfK)](2)}(2) and G(3) = Gly-Gly-Gly), (111)In(DOTA-RGD(4)) (RGD(4) = E{E[c(RGDfK)](2)}(2)) and (111)In(DOTA-3G-RGD(2)) (3G-RGD(2) = G(3)-E[G(3)-c(RGDfK)](2)) as new radiotracers for imaging integrin α(v)β(3)–positive tumors. The IC(50) values of DOTA-6G-RGD(4), DOTA-RGD(4) and DOTA-3G-RGD(2) were determined to be 0.4 ± 0.1, 1.5 ± 0.2 and 1.3 ± 0.2 nM against (125)I-c(RGDyK) bound to integrin α(v)β(3)–positive U87MG human glioma cells. (111)In(DOTA-6G-RGD(4)), (111)In(DOTA-RGD(4)) and (111)In(DOTA-3G-RGD(2)) were prepared by reacting (111)InCl(3) with the respective DOTA conjugate in NH(4)OAc buffer (100 mM, pH = 5.5). Radiolabeling could be completed by heating the reaction mixture at 100 °C for 15 – 20 min. The specific activity was ~1850 MBq/μmol for (111)In(DOTA-3G-RGD(2)) and ~1480 MBq/μmol for (111)In(DOTA-6G-RGD(4)). The athymic nude mice bearing U87MG human glioma xenografts were used to evaluate tumor uptake and excretion kinetics of (111)In(DOTA-6G-RGD(4)), (111)In(DOTA-RGD(4)) and (111)In(DOTA-3G-RGD(2)). The results from both the integrin α(v)β(3) binding assay and biodistribution studies suggest that the tetrameric cyclic RGD peptides, such as RGD(4) and 6G-RGD(4), are most likely bivalent in binding to the integrin α(v)β(3). Both (111)In(DOTA-6G-RGD(4)) and (111)In(DOTA-RGD(4)) had significantly higher tumor uptake than (111)In(DOTA-3G-RGD(2)) at 24 – 72 h post-injection due to the extra RGD motifs in RGD(4) and 6G-RGD(4). (111)In(DOTA-3G-RGD(2)) had very little metabolism while (111)In(DOTA-6G-RGD(4)) had a significant metabolism during its excretion via both renal and hepatobiliary routes over the 2 h period, probably due to its much larger size. The combination of high tumor uptake with long tumor retention suggests that their corresponding (90)Y and (177)Lu analogs M(DOTA-6G-RGD(4)) (M = (90)Y and (177)Lu) might be useful as therapeutic radiotracers for treatment of integrin α(v)β(3)-positive solid tumors.